Olhares sobre o patrimônio: a busca de significados da paisagem - Marina Salgado (2017)
The present thesis will seek to approach the landscape as a phenomenon, that is, the product of the relation between the subject and the object, having its construction influenced by the previous experience of this being, as well as questions referring to the natural aspects of the place, available techniques, economy, among others. All this complex interaction will be reflected in the construction of the landscape, that is, the landscape as a social formation will be imbued with meanings, which contribute to the establishment of the existencial foothold of man. Thus, it is assumed that the landscape is the support for the foundation of man's existence in the world, materializing as his existential space, and that from the understanding of its meanings, established by the subject-object relationship - the subject understood in this research as the social actors: residents and technicians of IEPHA / MG - these may collaborate to manage this landscape. In this sense, the landscape will not be considered as a mere object of contemplation, but first of all, considering the complexity of this concept, as an ideal object considering the various alternatives of its view, that is, the landscape as a noema. In this perspective, it will be evaluated the inclusion of the different attributions of meaning provided by the different views, in the process of reading, identification and knowledge of the landscape as a cultural heritage, which may change the method of management of the same. In order to do so, the listed historical centers for Institute of Historical and Artistic Heritage of Minas Gerais centers will be used as case study and later a cut in the city of Catas Altas wil be doing for the application of the search of the meaning of its landscape. In order to cover all the complexity of the landscape approach and its relation to man, the phenomenological method will be used, as well as the relation of the landscape to the existence of being and aesthetics, which will be the basis of all the research sought in this thesis. This theoretical and methodological foundation, phenomenology - existence - aesthetics, will guide the process of investigation of the intentions of meanings attributed to the landscape by both technicians of IEPHA / MG and by the inhabitants of Catas Altas, making it possible to establish a key of comparison between these two social agents and its impact on landscape management. From this reading, it is intended to point to new possibilities of integrated intervention strategies that consider the complexity of the landscape, its attributes, and its influence on the posture of man in the world, which may allow advancement in the challenging issue of urban conservation